The Expression of Different Micrornas in Iraqi Patients with Childhood Acute Leukemia and Their Association to C/EBP-Î’ Serum Level - Al Nakeeb, Rowshen Hani; Alrubaye, Dalal (Iraqi Journal of Science, 2020)
Leukemia is the most common cancer in children which causes death despite the high survival rate. Therefore, new methods are required to find a suitable therapy. A small RNA called microRNAs (miRNAs) is used as a biomarker for cancer diagnosis and early prognostic evaluation. Expression levels of three miRNAs from the 3' arm (miR-142-3p, miR-223-3p and miR-146-3p) were detected in serum samples from 30 acute leukemic children and from 30 healthy individuals by using qPCR. The miR-142-3p and miR-146-3p profiles were significantly downregulated (P=0.0010 and 0.0012, respectively), while miR-223 was found to be significantly upregulated (P= 0.0044) in the pateints. Serum level of C/EBP-Î² (CCAAT-enhancer-binding protein) was also determined by enzyme-linked immunosorbent assay (ELISA) and showed a significantly higher level in the patients (pâ‰¤0.0001). However, this higher enhancer level is probably not the reason for the abovementioned differences in miRNAs expression, as indicated by the weak correlation values with the three miRNA molecules (0.5737, 0.6625 and 0.7769, respectively). In conclusion, the fold change of miR-142-3p, miR-223-3p and miR-146-3p in serum could be potentially used as an early indicator of the occurrence of acute leukemia in children.